Commodity Markets Outlook, April 2017 - World Bank Group (World Bank, Washington, DC, 2017)
Prices for most industrial commodities strengthened further in the first quarter (q/q), while global agricultural prices remained broadly stable. Crude oil prices are forecast to rise to an average of $55 per barrel (bbl) in 2017 from $43/bbl in 2016. The oil forecast is unchanged since October 2016 and reflects balancing forces: upward pressure on prices from production cuts agreed by Organization of Petroleum Exporting Countries (OPEC) and non-OPEC producing countries, and downward pressure from persistently high stocks, supported by the faster-than-expected rebound of the U.S. shale oil industry. Metals prices are projected to increase 16 percent as a result of strong demand in China and various supply constraints, including labor strikes and contractual disputes in the case of copper, and environmental and export policies for nickel. Agricultural commodity prices, which gained 1 percent in the first quarter, are anticipated to remain broadly stable in 2017, with moderate increases in oils and meals and raw materials offset by declines in grains and beverages.